Genetic typing and intrafamilial transmission of human T-lymphotropic virus type 1 in non-endemic areas of China - Ji, Huimin; Chang, Le; Yan, Ying; Sun, Huizhen; Liu, Yi; Wang, Lunan (Frontiers in Microbiology, 2023)
The origin and intrafamilial transmission of Human T-Lymphotropic Virus Type 1 (HTLV-1) in the non-endemic population such as China is still unknown. In this study, donors from blood banks/centers in China(includes 28 provinces and Shenzhen city) during 2019 and 2021 were screened for HTLV-1/2 antibody and all the reactive samples were tested by a line immunoassay (LIA) and quantitative polymerase chain reaction (qPCR). Samples that can be detected by qPCR were amplified and sequenced for the long terminal repeat (LTR) region. The positive donors were contacted to identify their relatives. As a result, 4,451,883 blood donors were totally tested and 50 of them were confirmed to be HTLV-1/2 positive. Viral LTR sequences genotyped from 26 HTLV-1 carriers demonstrated that all had the HTLV-1a genotype, of which Transcontinental and Japanese subgroups accounted for half each. There were 17 family members of 11 index donors detected, and the HTLV-1 infection rate in the spouses of male index donors (83.3%, 5/6) was significantly higher than that in the husbands of female index donors (0.0%, 0/4). However, 7 children of HTLV-1 positive women were tested and found negative. Therefore, our findings indicated that HTLV-1 is spreading silently from high-endemic to low-endemic areas in China. In order to preventing further HTLV-1/2 transmission, an efficient HTLV-1/2 screening strategy and counseling of the viruscarriers are essential.